Pola Komunikasi Pernikahan Beda Etnis Jawa-Minang (Studi Deskriptif Kualitatif Pola Komunikasi Lintas Budaya Dalam Pernikahan Etnis Jawa-Minang) - Damayanti, Shavira Amellia; Indriastuti, Yudiana (Jurnal Representamen, 2022)
Abstract Ethnic marriage is a form of relationship between men and women who come from two different ethnic groups/races. Inter-ethnic marriages that occur of course go through many previous adaptation processes that exceed the process of adapting one-ethnic marriages, especially in terms of language and daily communication styles. The goal of this study was to ascertain how interethnic marriages between the Javanese and Minang ethnic groups affected the communication patterns. The Joseph A. Devito hypothesis of family communication patterns is used in this study's qualitative descriptive methodology. Four pairs of informants were interviewed in-depth as part of the used data collection technique. The communication equality pattern, balanced split pattern, and unbalanced split pattern are the three patterns that best describe the study's findings. One pair of informants agrees that the communication pattern they generate in the equation is truthful, open, direct, and free of opinion expression. There is also one pair of informants that claim to have authority over each area in their contacts with their spouses, such as the woman taking care of the children and cooking while the husband is responsible for earning a living, in a separate balanced communication pattern. Meanwhile, in a separate unbalanced communication pattern, there are two pairs of informants who agree that in the household there is only one individual who is dominant in decision making. However, in the monopoly pattern of communication, none of the eight informants represent the definition of this communication pattern because neither party feels monopolized. There is still a process of discussion in decision-making and neither one of them is ruling the other. Keywords: Intercultural Communication, Different Ethnic Marriages, Communication Patterns